COVID-19 and the impact of diabetic and obese patients during confinement - Nascimento, Iramar Baptistella do; Barboza , Erickson Zacharias; Fleig, Raquel (Medicina (Ribeirao Preto), 2023)
Objective: Identify aspects related to obesity and diabetes according to clinical and social factors combined with physical conditioning obstacles during the COVID-19 confinement routine. Methods: Database from PubMed/ MEDLINE, Web of Science, Scopus, LILACS, Embase and grey literature (Google Scholar) was used, as well as PRISMA, and Downs and Black checklist for bias risk analysis. To summarize the results, two subtitles were defined in line with the research objectives. Results: Seventeen studies were included for qualitative synthesis analysis: twelve sectional cohort studies, four cross-sectional and one multicenter retrospective. Obese and diabetic patients increased comorbidities when infected by COVID-19, due to compromising pathological interaction followed by complicationssuch as ketoacidosis, high hyperosmolarity infection, dyslipidemia and psychological disorders. Scientific findings show a higher level of hospitalization in Intense Care Units (ICU) for obese subjects compared to diabetics when infected by the new coronavirus. With lower physical activity and lack of motivation due to sedentary behavior, obese and/or diabetics show an adverse physical and mental prognostic during and after the end of pandemics. Conclusion: The specific understanding about immunomodulatory approach and enzymatic inhibitors is important for primary patient assistance. Multidisciplinary networks strategy must track individuals with a propensity to overweight and diabetes during social confinement, once it is difficult to keep glycemic and dyslipidemic control, which are unfavorable by anxiety, stress and the idea of economic bankruptcy.